Microstructural and mechanical development of As-cast and heat-treated 935AgCu alloys - S. Sakultanchareonchai (2018)
© 2017 Trans Tech Publications, Switzerland. Microstructural and mechanical development of the various heat-treated 935 Ag-Cu alloys were explored. The heat-treatment processes were applied viz. holding before quenching for 2 and 15 min, homogenization at 750 °C for 60 min followed by water quenching, and aging at 350 °C for 15 to 60 min followed by water quench. It was found that the specimens with copper addition gave a high resiliency in all heat treatment conditions however the effect of homogenization with aging treatment fostered deep blemish or fire scale on its surface. The amplifications of resiliency of 935 heat-treated AgCuSn and AgCuBe alloy were increased but elongation values were slightly reduced. The 935 AgCuBeSn specimens produced adequate resiliency and elongation after aging at 350 °C for 15 to 60 min followed by water quenching. Partial dissolution and spheroidization of eutectic phase were occurred by homogenization treatment at 750 °C. Aging treatment promoted precipitation of 3-20 nm fcc (Cu,Sn)-rich precipitates and engendered an improvement of hardness, yield strength and the modulus of resilience or resiliency.